2022
DOI: 10.1111/ctr.14878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of kidney transplant on post‐operative morbidity and mortality in patients with pre‐operative cardiac dysfunction

Abstract: Background Several studies show an increase in complications, both cardiac and non‐cardiac, and a higher mortality in patients with preexisting cardiac disease when they undergo elective surgery. Due to the high incidence of cardiac dysfunction in patients with concomitant chronic kidney disease, we wanted to determine if the same negative impact is demonstrated in patients undergoing kidney transplantation. Methods A retrospective analysis was done on 582 patients who underwent kidney transplant from a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Additionally, there was no difference in morbidity or mortality following kidney transplant in these patients compared to those with LVEF ≥40%. 17 The utility of cardiovascular screening in asymptomatic patients was another common area of study. Cheng et al demonstrated that pre-transplant testing for coronary heart disease within 12 months of transplantation was not associated with a reduction in the rate of death or acute myocardial infarction within 30 days of kidney transplantation (rate difference: 1.9%; 95% confidence interval (CI): 0%-3.5%) in a quasi-experimental cohort study using instrumental variable analysis of 79,334 kidney transplant recipients of whom 5.3% met one of the primary outcomes.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…Additionally, there was no difference in morbidity or mortality following kidney transplant in these patients compared to those with LVEF ≥40%. 17 The utility of cardiovascular screening in asymptomatic patients was another common area of study. Cheng et al demonstrated that pre-transplant testing for coronary heart disease within 12 months of transplantation was not associated with a reduction in the rate of death or acute myocardial infarction within 30 days of kidney transplantation (rate difference: 1.9%; 95% confidence interval (CI): 0%-3.5%) in a quasi-experimental cohort study using instrumental variable analysis of 79,334 kidney transplant recipients of whom 5.3% met one of the primary outcomes.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…Notably, mean EF improved significantly after transplant compared to pre-transplant in the EF <40% group (55.8% post-transplant vs 38.3% pre-transplant ( P < .0001), suggesting that KTx is beneficial in this population. 34…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…33 The effect of heart failure with reduced ejection fraction (EF) on outcomes following KTx was analyzed in a retrospective study of 573 patients. 34 Patients were divided into groups with normal EF (≥40%) and low EF (<40%). Survival at 3 years was similar between the 2 groups (93.7% in EF ≥40% vs 90.9% in EF <40%, P = .46).…”
Section: Cardiovascular Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Interestingly, it was also shown this year that patients with heart failure with reduced ejection fraction undergoing renal transplantation demonstrated an improvement in their ejection fraction postoperatively. 21 Rounding out the year in review pertaining to the care of kidney transplant patients was more evidence for the safety and efficacy of Sugammadex use in this population. Here, there was no negative impact on graft function, and Sugammadex administration was associated with shorter recovery room stays and lower rates of postoperative ICU admission and hypoxia.…”
mentioning
confidence: 99%